Guidelines for radioiodine therapy in differentiated thyroid cancer and post-therapeutic follow-up - A. Yu. Shurinov; E. V. Borodavina; V. V. Krylov; M. A. Sigov; A. A. Rodichev; S. A. Ivanov; A. D. Kaprin (Опухоли головы и шеи)
The radioiodine therapy is a one of the basic elements at combined treatment of differentiated thyroid cancer and is an alternative method for patients with distant metastases and a potentially high risk of tumor recurrence. It has been used in clinical practice for more than 80 years. The first report on the phenomenon of accumulation of 130I/131I in a metastatic focus of differentiated thyroid cancer was published by A. Keston et al. in 1942, and in 1946, the production of 131I was established, and the drug became available. In our country, radioiodine therapy has been widely used for the treatment of differentiated thyroid cancer since 1982.This article presents methodological recommendations for radioiodine therapy of patients with differentiated thyroid cancer, provides a modern examination algorithm, discusses the basic principles of laboratory, instrumental diagnostics and treatment approaches treatment of this disease.